Depressed Demand - Giang Nghiem (ZBW - Leibniz Information Centre for Economics, 2020)
Using a survey of Dutch households, we find that individuals who have experienced higher national unemployment rates over their lifetime save more and borrow less, after controlling for aggregate shocks, income, wealth, and demographics. These results are consistent with experience-based learning and inconsistent with rational learning. Furthermore, these individuals find it more important to save for retirement and are more worried about losing their job. These observations suggest that periods of high unemployment depress aggregate demand because of persistently more pessimistic beliefs.
Keywords: E21; E32; E71; 330